2014
DOI: 10.1136/thoraxjnl-2014-205944
|View full text |Cite
|
Sign up to set email alerts
|

High-intensity training following lung cancer surgery: a randomised controlled trial

Abstract: NCT01748981.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
192
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(219 citation statements)
references
References 37 publications
6
192
0
4
Order By: Relevance
“…The beneficial effects of rehabilitation in lung cancer patients, were currently limited to a few randomised trials. These trials showed that patients with lung cancer can improve their exercise capacity, muscle strength and QoL, however the results were not consistent [2,9,29].…”
Section: Introductionmentioning
confidence: 99%
“…The beneficial effects of rehabilitation in lung cancer patients, were currently limited to a few randomised trials. These trials showed that patients with lung cancer can improve their exercise capacity, muscle strength and QoL, however the results were not consistent [2,9,29].…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Further, there have been some randomized controlled trials, and a recent Cochrane review, that have investigated whether this impairment in exercise capacity can be ameliorated with exercise training. [11][12][13] Although there is interest in exercise capacity and the role of exercise training in this population, data exploring the responses to exercise in people following curative intent treatment for NSCLC are scarce. The cardiopulmonary exercise test (CPET) is a laboratory-based assessment, which provides a global assessment of an individuals' response to exercise.…”
Section: Introductionmentioning
confidence: 99%
“…A randomised controlled trial published in 2014, on patients who underwent lung cancer surgery employed high-intensity endurance and strength training (60 min, three times a week, 20 weeks), starting 5e7 weeks after surgery in the intervention group and found that it was well tolerated and led to significant improvements in peak oxygen uptake muscular strength, total muscle mass, functional fitness and quality of life. 19 The exercise regime employed in this study was longer in duration and higher in intensity as that in our study, but it is difficult to directly compare the two study groups. But it is safe to say that aerobic exercise whether done preoperatively or postoperatively plays some role in reduction of PPC and LOS.…”
Section: Discussionmentioning
confidence: 99%